LEXICAL AND SEMANTIC FEATURES OF IDIOMS IN MODERN ENGLISH AND UZBEK LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: By comparing the transparency, phonetic qualities, and universality of idioms in English and Uzbek, the article illustrates the distinct yet parallel ways that idiomatic expressions function within these languages. Ultimately, this study demonstrates that idioms are not just linguistic expressions but cultural artifacts that preserve and communicate shared values, historical contexts, and social norms of their respective societies.